Association of thyroid function with white coat hypertension and sustained hypertension. Issue 5 (11th April 2019) - Cai, Peng; Peng, Yan; Chen, YuXi; Li, Li; Chu, Wei; Wang, Yan; Wang, Xukai
Abstract : This study aimed to explore the relationship of thyroid‐stimulating hormone (TSH), free triiodothyronine (FT3), and free thyroxine (FT4) levels with hypertension subtypes. 1056 euthyroid adults were included as research samples. They underwent measurement of clinic blood pressure and 24‐hours ambulatory blood pressure monitoring. Then, they were divided into normotension (NT), white coat hypertension (WCH), masked hypertension (MHT), and sustained hypertension (SHT) groups. The 24‐hours dynamic electrocardiogram was performed to analyze the heart rate variability (HRV), so as to reflect the cardiac autonomic function. The relationship between hypertension subtypes, thyroid function, and HRV was analyzed. The TSH concentration was significantly higher in the SHT group than in the NT group ( P  = 0.001). The FT3 concentration was higher in the SHT group than in the NT and MHT groups ( P  = 0.013, P  = 0.008), while the FT4 concentration was significantly higher in the WCH group than in the NT group ( P  = 0.002). The changes in HRV were observed between the SHT, WCH, and MHT groups and the NT groups, as well as between the SHT and the MHT groups. The multiple linear regression analysis also showed that FT3, HRV (RMSSD and PNN50), and blood pressure levels linearly correlated with one another ( P  < 0.05). Meanwhile, the linear regression analysis showed a linear negative correlation between FT4 and HRV (SDANN) in the WCH + NT group ( P  = 0.001). Thyroid function was closely related to hypertension subtypes such as WCH probably due to the changes in the cardiac autonomic function.